Smart Restaurants - ., Vamseekrishna; Paruchuru Jyothshnasri, A; Aiswarya, Vuddagiri; Sameer, Shaik (International Journal of Engineering and Technology, 2018)
Conventional strategy that is utilized usually in hotels/restaurants is by taking the client's requests and recording it on a bit of paper and afterward giving the request in the kitchen area .The nourishment requesting framework is proposed with the utilization of a handheld gadget set on each table which is utilized to make a request at the eatery. The framework utilizes a push buttons in addition to show module which is put on every client table for them to make orders. Request is made by choosing the things showed on the mobile App. The request will be sent from the client segment utilizing ZigBee correspondence, and consequently will be shown on a screen at the kitchen. The bill will be shown with table number at the administrator/charging area. The task will lessen the time spent on making the requests and paying the bills, whereby the cost and labor likewise can be diminished.